Astrovirus evolution and emergence - Wohlgemuth, Nicholas (Infect Genet Evol, 2019)
Astroviruses are small, non-enveloped, positive-sense, single-stranded RNA viruses that belong to the Astroviridae family. Astroviruses infect diverse hosts and are typically associated with gastrointestinal illness; although disease can range from asymptomatic to encephalitis depending on the host and viral genotype. Astroviruses have high genetic variability due to an error prone polymerase and frequent recombination events between strains. Once thought to be species specific, recent evidence suggests astroviruses can spread between different host species, although the frequency with which this occurs and the restrictions that regulate the process are unknown. Recombination events can lead to drastic evolutionary changes and contribute to cross-species transmission events. This work reviews the current state of research on astrovirus evolution and emergence, especially as it relates to cross-species transmission and recombination of astroviruses.